Bomb radiocarbon determines absolute age of adult fin whales, and validates use of earplug growth bands for age determination - Campana, Steven E.; Finnsdóttir, Sigríður Vala; Sigurðsson, Guðjón Már (Frontiers in Marine Science, 2024)
Baleen whales are one of the few vertebrate taxa for which there are no confirmed estimates of longevity or methods of age determination. Lamina counts in the waxy earplug are assumed to represent age, but ageing accuracy is completely unknown. In this study, bomb radiocarbon assays of the earplug growth sequence in three adult fin whales (Balaenoptera physalus) were used to prepare the most complete within-individual bomb radiocarbon chronologies yet reported for any vertebrate. The whale radiocarbon chronologies matched those of known-age carbonate reference chronologies very well, indicating that the earplug laminae were both metabolically stable and formed throughout the life of the whale. Earplug lamina counts accurately represented absolute ages of 65-85 yr to within 6% of the correct age. Detection of a significant declining trend in δ13C with year of lamina formation within individual whales was consistent with that of the Suess effect, again underlining the metabolic stability of the earplug laminae. Given our results, recent applications of earplug laminae for reconstructing diet and life history events appear to be firmly based, with the potential for further elemental and isotopic applications analogous to those of the otolith.